Firearm Ownership & Storage Practices in Relation to Mental Health and Interpersonal Theory Constructs in Military Service Members & Veterans. (2nd January 2020) - Smith, Phillip N.; Fadoir, Nicholas A.; Currier, Joseph M.
Abstract: The objective of the current study was to inform the understanding of how firearms confer risk for suicide in military service members and veterans. Relations among firearm ownership and storage practices with mental health and interpersonal theory of suicide constructs were examined in a sample of 201 military service members and veterans using a cross-sectional survey design. Long gun, but not handgun, ownership was positively associated with fearlessness about death. Potential alcohol abuse was positively associated with handgun ownership, less secure storage practices, and refusal to answer questions about handgun ownership. Findings are consistent with recent ideation-to-action frameworks for understanding firearms as a transitional risk factor for suicide. However, other factors, such as attitudes toward health care, help-seeking, and governmental and provider motivations are also likely relevant in more fully understanding suicide risk in military service members and veterans.